iTRAQ-based quantitative proteomic reveals proteomic changes in Serratia sp. CM01 and mechanism of Cr(Ⅵ) resistance - Yuan Liu (Elsevier, 2021)
Objective: Serratia sp. CM01 is a wild strain with the resistance and reduction ability of chromium(Ⅵ). The aim of this study it to investigate the underlying mechanisms of the Cr(Ⅵ) tolerance and reduction of strain CM01, and to explore its response to environmental pollution pressure at the molecular level. Methods: The iTRAQ technique was utilized to investigate the differentially expressed protein patterns related to the Cr(Ⅵ)-resistance in wild-type strain CM01 and domesticated CM01. RT-qPCR was used to verify the expression levels of several functional genes. The cell surface hydrophobicity and autoaggregation, the intracellular glucose content, and the total superoxide dismutase (SOD) activity were determined. Results: In total, 2750 proteins were detected and identified in WT CM01 and domesticated CM01. Compared with WT CM01, the iTRAQ results of 646 proteins were found to be significantly differentially expressed in domesticated CM01. There were 343 up-regulated and 303 down-regulated proteins, which mainly related to carbohydrate metabolism, stress responses, amino acid metabolism and some other systems. RT-qPCR results showed that the expression level of seven genes in domesticated CM01 were consistent with the iTRAQ proteomic profiles. The cell surface hydrophobicity, self-aggregation, intracellular glucose content and total SOD activity of domesticated CM01 with Cr(Ⅵ) treatment were significantly higher than without Cr(Ⅵ) treatment. Conclusion: Domesticated CM01 displayed a complex biological network to exhibit the tolerance of Cr(Ⅵ), which may be attributed to the following aspects: (a) CM01 reduced the consumption of glucose by inhibiting the metabolism of carbohydrates, which was an energy-saving survival mode. (b) The inositol phosphate metabolism pathway played an important role. (c) Oxidative stress proteins enhanced the adaptability. (d) CM01 enhanced biosynthesis of hydrophobic amino acids to resistance to Cr(Ⅵ). (e) Several key systems and proteins, such as UvrABC system, Lon protease, porin OmpC, also may play an important role.